Study on the deep removal of phosphorus in the by-product salts of glyphosate by sedimentation method - Qisheng Wu; Sen Wang; Jie Zhang (Desalination and Water Treatment)
In this paper, phosphorus removal experiments were conducted on the by-product salt of glyphosate using a chemical precipitation process. The precipitates after chemical precipitation were characterized using microscopical techniques, including scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), and energy-dispersive X-ray spectroscopy (EDS). Investigated the phosphorus removal efficiency of the polyaluminum chloride (PAC) coagulant and evaluated the influence of various factors such as dosage, pH, and settling time. The experimental results indicate that when the ratio of polyaluminum chloride dosage to total phosphorus content is 10:1, with an initial solution pH of 7 and a settling time of 45 min, the phosphorus content in the glyphosate by-product salt solution can be reduced from 242 mg/L to 6.49 mg/L, achieving a phosphorus removal rate of 97.32%. Investigated the composite phosphorus removal of polyaluminum chloride (PAC) and polyacrylamide (PAM) and evaluated the influence of various parameters such as the type and dosage of polyacrylamide, pH, and settling time. The experimental results indicate that selecting cationic polyacrylamide with a molecular weight of 300,000, the dosage ratio of polyacrylamide to polyaluminum chloride is 1:6, initial pH is 7.5, and the settling time is 25 min can reduce the phosphorus content in the glyphosate by-product salt solution from 242 mg/L to 1.94 mg/L, achieving a phosphorus removal rate of 99.20%.